Roadside tree composition, origin status, and principal-use composition along selected urban corridors in Surakarta, Central Java, Indonesia - RAISA NOOR SAFIRA; KHOTROTUN NIDA FARIKHA; MARETTA PATRICIA BERNADETTA; MARTINA PUTRI MAHARANI; MUHAMMAD ADIB AL-DZAHABI; WHIDI HIMAWAN; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Safira RN, Farikha KN, Bernadetta MP, Maharani MP, Al-Dzahabi MA, Himawan W, Setyawan AD. 2026. Roadside tree composition, origin status, and principal-use composition along selected urban corridors in Surakarta, Central Java, Indonesia. Biodiversitas 27 (5): d270537. https://doi.org/10.13057/biodiv/d270537. Roadside trees are conspicuous elements of urban green infrastructure, but reliable inventories remain limited for many tropical secondary cities. This study provides a standardized descriptive assessment of roadside tree composition and principal use categories along selected corridors in Surakarta, Central Java, Indonesia. Twenty purposively selected 200-m transects, four in each of five sub-districts, were surveyed. Living arborescent perennials maintained as part of roadside structural vegetation were counted and identified, and each species was classified by origin status and principal roadside use. Diversity was summarized using Shannon diversity, Pielou evenness, Margalef richness, and pairwise Sørensen similarity; all indices were recalculated directly from the species-by-sub-district abundance matrix. The inventory recorded 743 individuals representing 67 species and 24 families. Fabaceae had the greatest species richness and abundance, followed by Arecaceae in both measures. Jebres contained the most species (37), Banjarsari the most individuals (190), and Laweyan the highest diversity (H′: 3.242; E: 0.912; Dmg: 7.114). Pairwise Sørensen similarity ranged from 0.269 to 0.686, with the strongest overlap between Pasar Kliwon and Serengan. Introduced taxa comprised 41 species (61.2%) and 496 individuals (66.8%), native taxa comprised 25 species (37.3%) and 245 individuals (33.0%), and one taxon represented by two individuals remained uncertain in origin status. Ornamental trees were the largest principal use group by species and abundance, followed by shade trees. The ten most abundant species represented 55.0% of all individuals, and the most abundant species accounted for 11.04%. These results provide a descriptive baseline for the surveyed 4 km of roadside corridors, not a city-wide census. Future inventories should retain transect-level data and incorporate georeferenced tree locations, size, condition, roadside constraints, and repeated monitoring to strengthen management and ecological inference.